Geology and tectonic development of the Bras d'Or suspect terrane, Cape Breton Island, Nova Scotia - Raeside, Robert P.; Barr, Sandra M. (Canadian Journal of Earth Sciences, 1990)
The Bras d'Or Terrane is defined in Cape Breton Island and consists of four distinctive components, (i) Low-pressure, regionally metamorphosed aluminous and calcareous gneiss of the Proterozoic Bras d'Or metamorphic suite is restricted to the southeastern part of the terrane. (ii) Late Proterozoic clastic-volcanic-carbonate units (Blues Brook, Malagawatch, McMillan Flowage, and Benacadie Brook formations, and Barachois River and Bateman Brook metamorphic suites) occur throughout the terrane and are generally at low metamorphic grades, although sillimanite grade has locally been achieved, (iii) A suite of 555–565 Ma calc-alkalic dioritic to granitic plutons was emplaced at pressures ranging from about 900 to less than 100 MPa. (iv) Early Ordovician granitic plutonism and Ordovician 40 Ar/ 39 Ar ages record regional heating.The Bras d'Or Terrane docked with the Mira Terrane to the southeast no earlier than the Ordovician. Cambro-Ordovician sedimentary rocks of the Mira Terrane appear locally to be thrust over the Bras d'Or Terrane. Mississippian sedimentary rocks overlap both terranes. The present boundary, the Macintosh Brook Fault, is mainly a Carboniferous feature. Docking with the Aspy Terrane to the northwest occurred along the Eastern Highlands shear zone and is constrained by a 375 Ma stitching pluton, the Black Brook Granitic Suite. Docking may have been initiated as early as 415 Ma, as indicated by reset 40 Ar/ 39 Ar ages near the boundary. The three Proterozoic components of the Bras d'Or Terrane have been recognized in the Brookville Terrane of southern New Brunswick, and Late Proterozoic gneiss, Late Proterozoic – early Cambrian calc-alkalic plutons and Ordovician granitic plutons have been reported in parts of the Hermitage Flexure of southern Newfoundland. The Bras d'Or Terrane may therefore be a regionally significant component of the northern Appalachian Orogen.